The Long Noncoding RNA Blnc1 Protects Against Diet-Induced Obesity by Promoting Mitochondrial Function in White Fat - Tang S (Dove Medical Press, 2020)
Shengjie Tang, Weifen Zhu, Fenping Zheng, Weiwei Gui, Wenjing Zhang, Xihua Lin, Hong Li Department of Endocrinology, The Affiliated Sir Run Run Shaw Hospital, Zhejiang University, School of Medicine, Hangzhou 310016, Zhejiang, People’s Republic of ChinaCorrespondence: Xihua Lin; Hong Li Email linxihua@zju.edu.cn; srrshnfm@126.comIntroduction: Long noncoding RNAs (lncRNAs) play critical regulatory roles in metabolic disorder. Whereas, the regulatory role of lncRNAs in mitochondrial function of white adipose tissue (WAT) is unknown.Materials and Methods: We investigated the role of Blnc1 in metabolic homeostasis and mitochondrial function of C57BL/6 mice fed a high-fat diet (HFD) for 12 weeks, followed by multi-point injection of adenovirus carrying Blnc1 into epididymal fat (eWAT). In vitro, mitochondrial biogenesis and function were analyzed in 3T3-L1 pre-adipocytes with Blnc1 overexpression or knockdown. Mechanically, RNA immunoprecipitation (RIP) and chromatin immunoprecipitation (ChIP) were used to highlight the molecular mechanism of Blnc1 in pre-adipocytes.Results: Gross eWAT weight was significantly decreased and insulin resistance was improved in HFD-Ad-Blnc1 mice. Mitochondrial biosynthesis was induced by Blnc1 in eWAT, as evidenced by an increased mitochondrial DNA and enhanced Mito-tracker staining. The expression of mitochondria-related genes was increased in eWAT, hepatic fatty acid oxidation was upregulated, and lipid deposition was reduced in HFD-Ad-Blnc1 mice. Knockdown of Blnc1 in 3T3-L1 pre-adipocytes resulted in mitochondrial dysfunction. The mechanistic investigation indicated that Blnc1 stimulated the transcription of Pgc1β via decoying hnRNPA1.Conclusion: Therefore, eWAT-specific overexpression of Blnc1 improves hepatic steatosis and systemic insulin sensitivity, likely by enhancing mitochondrial biogenesis and function.Keywords: lncRNA-Blnc1, mitochondria, white adipose tissue, obesity, ribonucleoprotein, Pgc1β